Physical and physiological demands of elite and sub-elite field hockey players - Buglione, A.; Ruscello, B.; Milia, R.; Migliaccio, G. M.; Granatelli, G.; D'Ottavio, S. (International Journal of Performance Analysis in Sport, 2013)
The purpose of this study was to compare the physiological and the physical characteristics of elite and sub-elite Italian male field hockey players.